A one-year survey of Neisseria gonorrhoeae isolated from patients attending an east London genitourinary medicine clinic: antibiotic susceptibility patterns and patients' characteristics. Issue 1 (February 1995) - Lewis, D A; Ison, C A; Livermore, D M; Chen, H Y; Hooi, A Y; Wisdom, A R
Abstract : OBJECTIVES–To collect epidemiological data on gonococcal infection in an east London genitourinary medicine (GUM) clinic; to perform antibiotic susceptibility testing on Neisseria gonorrhoeae isolates and relate results to patient data; to assess the efficacy of current first-line antibiotic therapy for treating gonorrhoea. METHODS–Gonococcal isolates were collected from 113 patients attending the GUM clinic at Newham General Hospital over a one year period. Isolates (104) were tested for susceptibility to various antibiotics. Plasmid profiles were obtained for penicillinase producing gonococci (PPNG) and isolates exhibiting high-level tetracycline resistance (TRNG). Epidemiological information was collected from clinic attenders by routine note-taking. RESULTS–PPNG (16) accounted for 15% of isolates tested, only three being acquired outside the United Kingdom (U.K.). Plasmid typing showed three types of beta-lactamase-encoding plasmids were represented (2.9 MDa, 3.2 MDa and 4.4 MDa). Amongst the non-PPNG isolates, high-level chromosomal resistance to penicillin (CMRNG) was found in 3.5%, intermediate resistance in 57.5% and full susceptibility in 39%. One isolate showed decreased susceptibility to ciprofloxacin (MIC = 0.06 mg/l). Three PPNG isolates also possessed a 25.2 MDa plasmid and expressed high-level tetracycline resistance encoded by tetM. All isolates were susceptible to cefixime, cefotaxime, azithromycin and spectinomycin. Most gonorrhoea (90%) was seen in local residents. The male:female case ratio was 2:1 with homosexually-acquired gonorrhoea accounting for only 3.5% of the total. Most patients (96%) had acquired gonorrhoea in the U.K.. A past history of gonorrhoea was more frequent in male patients. Concurrent chlamydial infection was seen in 31% females and 16% males. CONCLUSIONS–The high PPNG rate supports a previous decision to change first-line therapy from amoxycillin with probenecid to ciprofloxacin. There was no evidence of clinical treatment failure with ciprofloxacin. Cefixime, cefotaxime, azithromycin and spectinomycin all appear to be suitable alternative therapies. Acquisition of gonorrhoea abroad was associated with isolates exhibiting penicillin resistance but such isolates were also obtained from patients infected locally and without a history of foreign travel.